Knowledge of cognition and entrepreneurial intentions: implications for learning entrepreneurship in public and private universities - Lope Pihie, Zaidatol Akmaliah; Bagheri, Afsaneh; Abdullah Sani, Zaidatol Haslinda (Elsevier, 2013)
Cognitive perspective to entrepreneurship has recently received growing attention by educators and researchers. Yet, research on the association between knowledge of cognition and one's intention to become an entrepreneur is scarce. This study attempts to narrow the gap in the literature by examining university students’ knowledge of cognition capacity and their intentions to become entrepreneurs. The sample consisted of 722 students from public (n=331) and private universities (n=391) in Malaysia. The findings indicated that students from public universities scored higher in all dimensions of knowledge of cognition including declarative, procedural and conditional knowledge. However, entrepreneurial intentions of students from private universities were higher than their counterparts form public universities. These findings highlight the importance of understanding students’ knowledge of cognition capacity to improve their entrepreneurial learning and consequently their intentions to become entrepreneurs. Implications of the findings for entrepreneurship education and research and agendas for future studies are discussed.